Water Remediation from Pollutant Agents by the Use of an Environmentally Friendly Supramolecular Hydrogel. Issue 4 (8th March 2022) - Giuri, Demetra; D'Agostino, Simone; Ravarino, Paolo; Faccio, Davide; Falini, Giuseppe; Tomasini, Claudia
Abstract: The removal of Diclofenac sodium from waste waters has a high relevance since it belongs to the therapeutic group most commonly found in wastes. An aromatic‐free and low‐impact technology that efficiently entraps aqueous pollutants is highly desirable. We synthesised two Boc‐protected and aromatic‐free tripeptides (Boc‐L‐Ala‐Aib‐L‐Val‐OH and Boc‐L‐Val‐Aib‐L‐Val‐OH) and studied their ability to form gels with mixtures of water and alcohols, such as methanol, ethanol and 2‐propanol. Boc‐L‐Ala‐Aib‐L‐Val‐OH forms a strong hydrogel in 2‐propanol/water mixtures able to trap up to 97.8% of Eosin Y model molecule and up to 92.0% of Diclofenac sodium from aqueous solutions. The hydrogel is also thixotropic, thermoreversible and biocompatible. This outcome is very encouraging and paves the way to a new approach for developing new materials using aromatic‐free hydrogels, useful for water remediation. Abstract : An aromatic‐free and low‐impact technology that efficiently entraps aqueous pollutants is reported. We formed gels, using the aromatic‐free tripeptide Boc‐L‐Ala‐Aib‐L‐Val‐OH with mixtures of water and alcohols. The hydrogel formed in 2‐propanol/water traps up to 97.0% of Eosin Y and up to 88.6% of Diclofenac sodium from aqueous solutions. The hydrogel is also thixotropic, thermoreversible and biocompatible.